Stargazing - Clumpas, Judith (Auckland University of Technology, 2020)
This thesis consists of practice-led research in the form of a full-length script for a feature film, plus a 6,000 word exegesis. A summary of the script follows: Rick travels for work, Annie is a stay at home mum, with a difference: He is a globally successful musician, and home for Annie and teenage Violet is a remote off-grid island in the South Pacific. The night sky is Violet’s passion, a symbol of her curiosity about the world outside. Two worlds collide when Annie’s utopia is disrupted by evidence of Rick’s wild living and infidelity, triggering her to reluctantly leave the island for the first time in a decade and take Violet to London. Once there, she discovers all is not as it appeared. Rick’s career is on the skids, and his longterm manager, Simon, Annie’s one time employer, has dropped him. Following the suicide of his long-time collaborator, Rick’s self-doubt has led to frequent anxiety attacks. He seeks career help from new songwriting partner Ophelia, who Annie can only see as a manipulative sexual predator. Meanwhile, Violet, the innocent child of an old-fashioned childhood, is smitten with the outside world, and desperate for friendship, idolising Ariadne, the precocious daughter of Ophelia. We learn Annie’s revulsion for London and the music industry stems from her youth, when as Simon’s employee she was subjected to unwanted sexual advances. She discovers, despite initial misgivings, that London culture has changed for the better, and gains confidence in tackling Simon’s sharp business practice, finding unexpected support from women in the business. Matters come to a head at a music festival, when Annie is able to prevent history repeating for Simon’s vulnerable receptionist, and witness his public humiliation at the hands of a girl band. Annie’s mistake in allowing Violet and Ariadne the freedom to wander around the festival site backfires, exposing Ariadne’s bullying. The potential loss of Violet forces Rick to choose between family and career, and he realises he needs to let Annie into his world. Annie learns to fight for what is right instead of running away, and there is hope that the family will find balance. The script is framed by an exegesis which is a 6,000 word essay on the subject of i) A comparative study of the genre of family drama. ii) The development process from synopsis to second draft.
Keywords: Screenplay; Marriage; metoo; Music